1864 Conn. Acts 95 - (:unkn) unknown (My University, 1864)
An Act In Addition To And In Alteration Of "An Act Relating To The Militia," chap. 73, § 8: It shall be the duty of the quartermaster general to provide a suitable armory for each company of active militia, upon a certificate from the adjutant general, that such company has organized according to law, and has made requisition for an armory, through the commanding officer of said company, as a drill room and place to preserve its arms and equipments; and also to provide for the expenses of cleaning and keeping in good repair the said arms and equipments, in such manner as he may prescribe.
Keywords: ARMED FORCES